Cloud Based Requirements Management Tools Should Be Selected on the Basis of Project Requirements - Siddiqui, Shams Tabrez; Ahmad, Md Oqail; Shuaib, Mohammad; Rizvi, S. Gulzar Ahmed (International Journal of Computer Sciences and Engineering, 2020)
Requirements engineering plays an important role in coordinating with various stakeholders / customer expectations and ensures developers build applications that meets virtually all stakeholder / customer requirements. Appropriate requirements management tool results in a better solution for the organizations' defined problem. Handling several thousands of requirements needs a Requirements management tool, so handling is a daunting task. This paper discusses the web-based requirements management tool that can easily trace requirements, online tender management, bug and defect, use cases and related information throughout the project's planning and development process. It has the centralized database; the solution can be updated from solitary consign. It can be easily used with any software development processes including, Waterfall, Spiral and Agile. This paper considers six leading Web based Requirements Management tools; IRIS Business Architect, ACCOMPA, JAMA Contour, Gatherspace, AgileSpecs, Blueprint, ReQtest, Orcanos and CASE Spec. It discusses their features including collaboration, History, Tracking, and Comments for Requirements, Status Reporting, Traceability, and Centralized database, Import /Export Data, Summary Reports and User Defined Attributes. Besides this, the paper also focuses on Project management attributes; regaining project control, reduce project risks, and decrease failure costs.